Sleepwalking into the 'Post-Racial': Social Policy and Research-Led Teaching. Issue 1 (14th January 2022) - Phillips, Coretta; Williams, Fiona
Abstract : Research-led teaching is the sine qua non of the 21 st century university. To understand its possibilities for teaching and learning about race in Social Policy requires, as a first step, interrogating the epistemological and theoretical core of the discipline, as well as its organisational dynamics. Using parts of Emirbayer and Desmond's (2012 ) framework of disciplinary reflexivity, this article traces the discipline's habits of thought but also its lacunae in the production of racial knowledge. This entails focusing on its different forms of institutionalised and epistemological whiteness, and what has shaped the omission or marginalisation of a full understanding of the racialisation of welfare subjects and regimes in the discipline. Throughout, the article offers alternative analyses and thinking that fully embrace the historical and contemporary role of race, racism, and nation in lived realities, institutional processes, and global racial orders. It concludes with pointers towards a re-envisioning of Social Policy, within a framework in which postcolonial and intersectional theory and praxis are championed. Only then might a decolonised curriculum be possible in which race is not peripheral to core teaching and learning.